a)
[tex] \frac{12 - x}{4} = \frac{x + 4}{12} \\ 4(x + 4) = 12(12 - x) \\ 4x + 16 = 144 - 12x \\ 16x = 128 \\ x = 8[/tex]
b)
[tex] \frac{3x - 2}{4} = \frac{4x - 5}{3} \\ 3(3x - 2) = 4(4x - 5) \\ 9x - 6 = 16x - 20 \\ 14 = 7x \\ x = 2[/tex]
c)
[tex] \frac{x - 3}{6} = 2(3x + 1) \\ \frac{x - 3}{6} = 6x + 2 | \times 6 \\ x - 3 = 36x + 12 \\ - 35x = 15 | \div ( - 35) \\ x = - \frac{15}{35} = - \frac{3}{7} [/tex]
d)
[tex]3(1 - \frac{x}{3} ) = \frac{5x - 1}{9} \\ 3 - x = \frac{5x - 1}{9} | \times 9 \\ 27 - 9x = 5x - 1 \\ 28 = 14x \\ x = 2[/tex]